First record of saucer scallop Ylistrum balloti (Bernardi, 1861) from equatorial South China Sea - Morni, W. Z. W.; Abit, L. Y.; Latif, K.; Nerurkar, S.; Ruhana, Hassan; Al–Asif, A. (Archives of Zoological Miscellany, 2022)
First record of saucer scallop Ylistrum balloti (Bernardi, 1861) from equatorial South China Sea. Ylistrum balloti is one of the Pectinidae species distributed within the Indo–Pacifc region. Recently, 15 live specimens of Y. balloti were recorded from the continental shelf of Sarawak, Malaysia. The main morphological characteristics were displayed on the outer valve, these being a brown–red colour and a clear concentric pattern of thin brown lines. The prominent internal ribbing numbers on both valves also helped species identifcation. The preliminary report of Y. balloti revealed that the species is present in Sarawak waters and can be further explored in the future.